A novel C-type lectin from spotted knifejaw, Oplegnathus punctatus possesses antibacterial and anti-inflammatory activity. Issue 92 (September 2019) - Liu, Xiaobing; Li, Xuemei; Peng, Meiting; Wang, Xuangang; Du, Xinxin; Meng, Lihui; Zhai, Jieming; Liu, Jinxiang; Yu, Haiyang; Zhang, Quanqi
Abstract: C-type lectin is a type of carbohydrate-binding protein and plays significant roles in innate immune response against pathogen infection. To date, thousands of C-type lectin had been identified in teleost. In the present study, we isolated a novel isoform of C-type lectin (OppCTL) from spotted knifejaw ( Oplegnathus punctatus ). The OppCTL encoded a typical Ca 2+ -dependent carbohydrate-binding protein, and was mainly expressed in liver in a tissue specific fashion. The expression of OppCTL was significantly up-regulated following Vibrio anguillarum infection in vivo, suggesting involvement in immune response. Hemagglutination analysis showed that the recombinant OppCTL (rOppCTL) could agglutinate erythrocyte from Mus musculus, Oplegnathus punctatus, Sebastes schlegelii and Paralichthys olivaceus . The rOppCTL could bind and agglutinate all tested bacteria. The rOppCTL possessed capacities of calcium-dependent agglutination to all tested bacteria. Sugar binding assay revealed that rOppCTL could also bind to the glycoconjugates of the bacterial surface, including lipopolysaccharide and peptidoglycan. Interestingly, Dual-luciferase analysis revealed that OppCTL could inhibit the activity of NF-κB in HEK-293T cells after OppCTL overexpression. Taken together, these results indicate that OppCTL has immune activity capable of defending invading pathogens and possesses potential immunoregulatory activity, enriching our understanding of the function of C-type lectin. Highlights: A novel C-type lectin OppCTL was cloned from spotted knifejaw Oplegnathus punctatus. V. anguillarum could significantly up-regulate the expressions of OppCTL in liver. Recombinant OppCTL can bind to all tested bacteria in the presence of Ca 2+ . Recombinant OppCTL can agglutinate not only all tested bacteria but mouse and fish erythrocyte in the presence of Ca 2+ . OppCTL could inhibit NF-κB activity in HEK-293T cells.